Charmless Bc⃗VV decays in the QCD factorization approach. (14th July 2017) - Chang, Qin; Wang, Na; Sun, Junfeng; Han, Lin
Abstract: In this paper, we present a study of the charmless B c → VV ( V denotes the light ground SU ( 3 ) vector meson) decays within the framework of QCD factorization. In the evaluation, two different schemes for regulating the end-point divergence are adopted. One (scheme I) is to use a parameterization model, which is usually employed in the QCD factorization approach; the other (scheme II) is based on the infrared finite gluon propagator of the Cornwall prescription. It is found that, in the annihilation amplitudes, the end-point divergence appears only in the power-suppressed corrections related to the twist-3 distribution amplitudes of the V -meson. The strengths of the annihilation amplitudes evaluated in scheme II are generally larger than those in scheme I. Numerically, in the decay modes considered in this paper, the CKM-favored B c → ρ − ω, K * − K * 0 decays have relatively large branching fractions, ∼  ( 10 − 7 ), and hence are likely to be the first observed by future experiments. In addition, all of the decay modes are dominated by the longitudinal polarization state; numerically, f L ( B c → VV ) ≳ 99 % .